IL-17C contributes to NTHi-induced inflammation and lung damage in experimental COPD and is present in sputum during acute exacerbations - Vella, Giovanna (PLoS One, 2021)
Neutrophilic inflammation results in loss of lung function in chronic obstructive pulmonary disease (COPD). Gram-negative bacteria, such as nontypeable Haemophilus influenzae (NTHi), trigger acute exacerbations of COPD (AECOPD) and contribute to chronic lung inflammation. The pro-inflammatory cytokine interleukin-17C (IL-17C) is expressed by airway epithelial cells and regulates neutrophilic chemotaxis. Here, we explored the function of IL-17C in NTHi- and cigarette smoke (CS)-induced models of COPD. Neutrophilic inflammation and tissue destruction were decreased in lungs of IL-17C-deficient mice (Il-17c(-/-)) chronically exposed to NTHi. Numbers of pulmonary neutrophils were decreased in Il-17c(-/-) mice after acute exposure to the combination of NTHi and CS. However, Il-17c(-/-) mice were not protected from CS-induced lung inflammation. In a preliminary patient study, we show that IL-17C is present in sputum samples obtained during AECOPD and associates with disease severity. Concentrations of IL-17C were significantly increased during advanced COPD (GOLD III/IV) compared to moderate COPD (GOLD I/II). Concentrations of IL-17A and IL-17E did not associate with disease severity. Our data suggest that IL-17C promotes harmful pulmonary inflammation triggered by bacteria in COPD.